TiO(2)@C core-shell nanoparticles formed by polymeric nano-encapsulation - Vasei, Mitra (Frontiers Media S.A., 2014)
TiO(2) semiconducting nanoparticles are known to be photocatalysts of moderate activity due to their high band-gap and high rate of electron-hole recombination. The formation of a shell of carbon around the core of TiO(2), i.e., the formation of TiO(2)@C nanoparticles, is believed to partly alleviate these problems. It is usually achieved by a hydrothermal treatment in a presence of a sugar derivative. We present here a novel method for the formation of highly uniform C shell around TiO(2) nanoparticles. For this purpose, TiO(2) nanoparticles were dispersed in water using an oligomeric dispersant prepared by Reversible Addition-Fragmentation chain Transfer (RAFT) polymerization. Then the nanoparticles were engaged into an emulsion polymerization of acrylonitrile, resulting in the formation of a shell of polyacrylonitrile (PAN) around each TiO(2) nanoparticles. Upon pyrolysis, the PAN was transformed into carbon, resulting in the formation of TiO(2)@C nanoparticles. The structure of the resulting particles was elucidated by X-Ray diffraction, FTIR, UV-VIS and Raman spectroscopy as well as TEM microscopy. Preliminary results about the use of the TiO(2)@C particles as photocatalysts for the splitting of water are presented. They indicate that the presence of the C shell is responsible for a significant enhancement of the photocurrent.